A bioenergetic approach favors the preservation and protection of prey, not cooking, as the drivers of early fire - Ben-Dor, Miki; Barkai, Ran (Frontiers in Nutrition, 2025)
IntroductionThe use of fire marks a critical milestone in human evolution, with its initial purposes debated among scholars. While cooking is often cited as the primary driver, this study proposes that meat and fat preservation, and predator protection were more likely the initial motivations for fire use by Homo erectus during the Lower Paleolithic (1.9–0.78 Ma).MethodsEmploying a bioenergetic approach, we compared the energetic returns of hunting versus plant gathering using ethnographic data, adjusted for Lower Paleolithic conditions. Caloric content of East African prey was calculated to assess consumption duration. Archeological evidence from early fire sites was analyzed for associations with large fauna.ResultsHunting large prey (>100 kg) yielded significantly higher energetic returns (16,269 ca/h) than plant gathering (1,443 ca/h), with megaherbivores like hippopotamus providing sustenance for up to 22 days for a group of 25. Early fire sites consistently contained large fauna remains, suggesting prolonged prey consumption. Cooking offered modest energetic gains (e.g., ~1,200 ca/h for meat), insufficient to offset fire maintenance costs, unlike preservation and protection.DiscussionThe substantial energetic disparity supports hunting as a dominant subsistence strategy, with fire enhancing efficiency by preserving meat and deterring predators. The prevalence of megaherbivores in Lower Paleolithic sites and heightened predation risks underscore these priorities over cooking, which likely emerged as a secondary benefit. Ethnographic analogies underrepresent these dynamics due to megafaunal extinctions altering the environment and prey availability.ConclusionMeat preservation and predator protection, rather than cooking, were likely the primary drivers of early fire use, aligning with Homo erectus’ specialization in large prey acquisition. This reframes fire’s role in human evolution, suggesting it supported a hypercarnivorous lifestyle and potentially influenced cognitive development.